2019
DOI: 10.1021/acs.jpca.8b11725
|View full text |Cite
|
Sign up to set email alerts
|

Same Charge Polaron and Bipolaron Scattering on Conducting Polymers

Abstract: We study the dynamics of scattering of two positive polarons moving toward each other with parallel spins and of a polaron and a bipolaron both with positive charges and different velocities, in single chains of cis-polyacetylene and polyparaphenylene. We use the Su−Schrieffer−Heeger model with Hubbard extensions solved within of the time-dependent Hartree−Fock approximation to account for electron−electron interactions, developed over a hexagonal lattice. The main results are elastic scattering in most cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the carrier size imposes influence over transport capabilities. 34,51,52,62 For GNRs and conjugated polymers, wider quasiparticles are likely to be more mobile than strongly localized carriers. Here, we extend this reasoning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the carrier size imposes influence over transport capabilities. 34,51,52,62 For GNRs and conjugated polymers, wider quasiparticles are likely to be more mobile than strongly localized carriers. Here, we extend this reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…Such behavior is characteristic of conjugated materials. The pivotal implication is that bipolarons tend to possess a greater effective mass in comparison to polarons. , This behavior is expected to persist in the B4A system.…”
Section: Resultsmentioning
confidence: 99%
“…It is natural since the effective mass of the bipolaron is about four times that of the polaron. 52,53 A small amount of charge transfers to the two edge chains (chain 1 and chain 3) and also moves periodically.…”
Section: Resultsmentioning
confidence: 99%
“…With such a description in hand, we can now investigate the relationship between the effective mass of the bipolaron in the system ( ) and the electron-phonon coupling as well as to the electric field. For the calculation of the effective mass, we considered the same scheme as employed for the calculation of the effective mass of the polaron and bipolaron in cis-polyacetylene and poly-pphenylene (PPP) [49], i.e., the equality between impulse and linear momentum variation (Δ ⃗ = ⃗ Δ ). The electric field was turned on adiabatically so that to avoid artificial numerical effects [50].…”
Section: Resultsmentioning
confidence: 99%